A Qualitative Study on Digital Aesthetics and Sound Interaction - Yalcin Yildirim; Mahyar Arefi (Multimodal Technologies and Interaction)
Many disciplines—from science to art and education—engage with the postdigital concept, where human activities transform into digital activities. The post-COVID-19 era has involved new consequences for societies, where education has increasingly utilized online platforms. Having said that, online pedagogy, with the directions and discourses of the senses, particularly visual and aural, remains under-explored. Studies have addressed the educational implications of the aural sense, but this study explores the nexus between digital aesthetics and sound pedagogy and delves deeper into students’ primarily descriptive learning outcomes. A multi-disciplinary class covered aesthetic terminologies, followed by a series of digital arts that envisioned digital, aesthetic, and listening practices. Considering the global agenda’s recent “new norms”, this study contributes to the postdigital era of sound and acoustic-related sciences.